1995
DOI: 10.1515/jpme.1995.23.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, immunosupression and reactivation of latent toxoplasmosis

Abstract: Toxoplasmosis is a chronic, latent infection which can be reactivated in the presence of immunosuppression. The critical question in obstetrics is whether toxoplasmosis may be reactivated in the presence of the physiological "immunosuppression" of pregnancy. Standard in vitro tests, done in 24 healthy pregnant women and compared with the literature, show no significant changes in humoral and cellular immunity during pregnancy. However, the fact that some infections occur more frequently and more severely than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…A case of CT was earlier reported in an HIV-infected pregnant woman who responded well with a standard regimen of pyrimethamine and sulfadiazine, with a normal fetal outcome (Hedriana et al, 1993). Another case of CT was confirmed in an HIV-infected pregnant woman during the puerperium with her CD4 count being < 200 cells/cumm (Biedermann et al, 1995). A prophylactic treatment was recommended to prevent maternal reactivation and congenital transmission of toxoplasmosis in such a case.…”
Section: Congenital Toxoplasmosismentioning
confidence: 96%
“…A case of CT was earlier reported in an HIV-infected pregnant woman who responded well with a standard regimen of pyrimethamine and sulfadiazine, with a normal fetal outcome (Hedriana et al, 1993). Another case of CT was confirmed in an HIV-infected pregnant woman during the puerperium with her CD4 count being < 200 cells/cumm (Biedermann et al, 1995). A prophylactic treatment was recommended to prevent maternal reactivation and congenital transmission of toxoplasmosis in such a case.…”
Section: Congenital Toxoplasmosismentioning
confidence: 96%
“…Antimicrobial treatment after maternal seroconversion is ineffective, possibly because transmission may occur before detection of seroconversion or because of antibiotic catabolism [6][7][8][9]. Reactivation of latent disease, secondary to maternal immunosuppression (such as AIDS) or corticosteroid therapy, may also result in fetal infection [10]. Severity of the disease correlates with the extent of placental damage [11].…”
mentioning
confidence: 99%
“…The high seroprevalence of toxoplasmosis in HIV infected patients might partly be due to early child hood and teenage infection. In contrast, Biedermann [BIEDERMANN et al, 1995] and Woldemichael [WOLDEMICHAEL et al, 1998] reported similar seroprevalence rates between HIV infected individuals and normal controls. As age increased, it was observed that there was a relative increase in seroprevalence due to exposure to infective stages of parasite.…”
Section: Resultsmentioning
confidence: 89%